2019
DOI: 10.21147/j.issn.1000-9604.2019.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic treatment on patients with severe dysplasia/carcinoma in situ of esophageal squamous cell carcinoma: A prospective cohort study

Abstract: Objective To explore the natural history of severe dysplasia/carcinoma in situ (SD/CIS) patients and to evaluate the efficacy of endoscopic treatment to SD/CIS patients. Methods Between January 2005 and December 2009, a population-based prospective screening program on esophageal squamous cell carcinoma (ESCC) was performed in Linzhou, China, with endoscopic screening plus iodine staining. All the eligible histologically confirmed SD/CIS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This is currently the best early screening method. 17 The central government expanded the scope of subsidies to local public health funds in 2005, including the screening, early diagnosis and treatment of esophageal cancer implemented in 2006. 18 The tumor stage at diagnosis was associated with the prognosis of esophagus cancer, and early detection could effectively reduce its mortality.…”
Section: Urban Male Urban Female Rural Male Rural Femalementioning
confidence: 99%
“…This is currently the best early screening method. 17 The central government expanded the scope of subsidies to local public health funds in 2005, including the screening, early diagnosis and treatment of esophageal cancer implemented in 2006. 18 The tumor stage at diagnosis was associated with the prognosis of esophagus cancer, and early detection could effectively reduce its mortality.…”
Section: Urban Male Urban Female Rural Male Rural Femalementioning
confidence: 99%
“…For patients with SD/CIS, 1 study pointed out that approximately 75% of those with untreated SD/CIS progressed to ESCC after 13 years of follow‐up, and endoscopic treatment was necessary for the majority of such patients, 5 which may induce overtreatment issues. However, another study reported a progression rate of only 10.7% for patients with untreated SD/CIS and 3.2% for those who were treated after an 11‐year follow‐up 20 . The results seem to be quite different, and it is difficult to tell which is more accurate at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and development characteristics of ESCC provide opportunities for screening. Almost all grades of squamous dysplasia and CIS are strongly associated with an increased risk of ESCC and can be used as an intermediate endpoint for screening 15,20 . Significant improvements in survival can be seen when the disease is confined to the superficial mucosa, and the progression to cancer can be stopped if treatments are given before invasion 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown increasing risks of progression in those with mild-, moderate-and severe dysplasia (7,8). Successful endoscopic treatment of dysplasia has been demonstrated in recent studies (9)(10)(11)(12), opening the possibility of preventing ESCC by finding and treating severe dysplasia in high-risk individuals.…”
Section: Introductionmentioning
confidence: 99%